2002
DOI: 10.1002/jclp.1153
|View full text |Cite
|
Sign up to set email alerts
|

Forgiveness and romantic relationships in college: Can it heal the wounded heart?

Abstract: This study evaluated the effects of two versions of a six-week group forgiveness intervention for college women who had been wronged in a romantic relationship. Participants (N = 58) were randomly assigned to a secular, religiously integrated, or no-intervention comparison condition. Participants completed a variety of forgiveness and mental health measures at one-week pretest, one-week posttest, and six-week follow-up. Participants in both intervention conditions improved significantly more than did those in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
171
0
11

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(188 citation statements)
references
References 29 publications
6
171
0
11
Order By: Relevance
“…Taylor et al (2007) explain one of the reasons of aggression as the expectation of revenge. On the other hand, Rye and Pargament (2002) relate forgiveness to the situation in which the person considered as a victim gives positive reactions such as mercy, rather than revenge and aggression, to the guilty person. As a result, it is observed that it is not possible to forgive and show aggression at the same time.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Taylor et al (2007) explain one of the reasons of aggression as the expectation of revenge. On the other hand, Rye and Pargament (2002) relate forgiveness to the situation in which the person considered as a victim gives positive reactions such as mercy, rather than revenge and aggression, to the guilty person. As a result, it is observed that it is not possible to forgive and show aggression at the same time.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%
“…Aunque son muchos los factores que influyen en que el proceso de perdonar se consiga o no, aquellos que tradicionalmente han sido objeto de estudio tienen que ver con el tipo de ofensa (Fincham, Jackson y Beach, 2005;Rye y Pargament, 2002), las características del ofensor (Bachman y Guerrero, 2006;Fincham et al, 2005;McCullough et al, 1997;Wade y Worthington, 2003;Zechmeister, García, Romero y Vas, 2004) (Allemand, Amberg, Zimprich, y Fincham, 2007;Cann y Baucom, 2004;Kachadourian, et al, 2004;McCullough, Rachal, Sandage, Worthington, Brown y Hight, 1998;Tsang, McCullough y Fincham, 2006). En el ámbito de la violencia de género, el papel del perdón se relaciona tradicionalmente con la permanencia de la víctima en una relación de maltrato o, si se ha producido la ruptura de la pareja, con una mayor probabilidad de retomar la relación con el maltratador.…”
Section: Antecedentesunclassified
“…En relación a las características de la ofensa, se ha observado que el perdón sería menos probable mientras más severa es evaluada aquella (Fincham y cols., 2005;Rye y Pargament, 2002).…”
Section: Estudios Sobre El Perdónunclassified